2000
DOI: 10.4049/jimmunol.165.1.182
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 and IFN-γ Up-Regulate Substance P Receptor Expression in Murine Peritoneal Macrophages

Abstract: While the ability of macrophages to express authentic substance P receptors (i.e., NK-1 receptors) has been inferred from radioreceptor binding assays and functional assays and, most recently, by identification of NK-1 receptor mRNA expression, we know little about NK-1 expression at the protein level or what host factors might up-regulate expression of this receptor. In the present study we demonstrate that the cytokines IL-4 and IFN-γ can increase the expression of NK-1 receptors on murine peritoneal macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 72 publications
3
68
0
Order By: Relevance
“…As shown in this report, one point of control is through transcriptional regulation of the biosynthesis of its natural ligand NK-1R (12,26). Also, engagement of SP with its receptor at the cell surface results in temporary receptor desensitization and loss of bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in this report, one point of control is through transcriptional regulation of the biosynthesis of its natural ligand NK-1R (12,26). Also, engagement of SP with its receptor at the cell surface results in temporary receptor desensitization and loss of bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…SP increases the functional phagocytic response in macrophages and other phagocytes (4). SP specifically activates NF-B, a key transcriptional factor involved in the control of cytokine expression (5,6). SP stimulates immune cells to produce inflammatory cytokines, including IL-1, IL-6, TNF-␣ (1), IFN-␥ (7), and macrophage inflammatory protein 1␤ (8), which are important constituents of immune cell activation and act as physiological induction signals in the regulation of immune responses.…”
mentioning
confidence: 99%
“…For example, substance P elicits the production of cytokines including TNF-α (Lotz et al, 1988), and IFN-γ (Lighvani et al, 2005) which are linked to the control of HSV-1 infection. As T and B lymphocytes and monocyte/macrophages express the NK1R (Stanisz et al, 1987;Pascual et al, 1992;Marriott and Bost, 2000), it has been suggested substance P may serve to optimize the local inflammatory response (Marriott and Bost, 2000) which may facilitate the clearance of pathogens (Brogden et al, 2005;Svensson et al, 2005) but have detrimental consequences relative to sites sensitive to inflammation as is the case of rheumatoid arthritis (Miller et al, 2000) and most likely, the CNS. In contrast to what has been reported, we found an elevation in substance P was associated with a reduction of IFN-γ in the TG but not BS of HSV-1-infected, sympathectomized mice.…”
Section: Discussionmentioning
confidence: 99%